Urgensi Kebijakan Pembatasan Sosial Berskala Mikro (PSBM) Pasca Pembatasan Sosial Berskala Besar (PSBB) Dalam Penanganan Covid 19 Di Kota Pekanbaru Tahun 2020 - Tito handoko; Harapan Tua RFS; Zulfa Harirah MS; Dahlan Tampubolon (Kemudi, 2021)
After the implementation of Large-Scale Social Restrictions, Pekanbaru City enters the New Normal condition based on the Pekanbaru Mayor Circular regarding the new normal life order. The new life order policy or New Normal actually led to an increase in COVID 19 cases, therefore the Pekanbaru City Government issued a micro-scale social restriction policy, especially in sub-districts that were considered to have the highest rate of spread of COVID 19. This study aims to determine the urgency of micro-scale social restriction policy. The method in this research uses qualitative methods by collecting data sources from legal products, articles and news from the mass media as well as interviews with research sources. The results of this study indicate that the urgency of the presence of this Micro-Scale Social Restriction policy is seen in two ways. First, as an initial step for community habituation in facing the new life order or the new normal. The community is not ready to live in a new normal framework so that less-reaching habituation is needed, namely micro-scale social restrictions. Second, the micro-scale social restriction policy was able to reduce the number of health protocol violations. However, it turns out that the decrease in the number of health protocol violations has no correlation with the decrease in the number of positive COVID cases. For 2 reasons, the implementation of this policy was in fact ineffective in suppressing the spread of COVID 19 in Pekanbaru City so that its enforcement was stopped.